2021
DOI: 10.3390/su13179883
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Moderators of the Influence of Enablers on Participation in Knowledge Sharing in Virtual Communities

Abstract: Virtual communities (VCs) are emerging as a cyberspace where active knowledge exchange between people occurs without time or space constraints. For VCs to be sustainable, a major challenge is ensuring that members voluntarily contribute and share knowledge. Therefore, many VCs provide anonymity as a means of encouraging members to participate more in knowledge-sharing activities. Given the recent prevalence of anonymity-based VCs, this study aimed to examine what has a significant impact on human behavior, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 68 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…This study provides a theoretically grounded explanation and offers a new perspective on the underlying nature of lurkers in OICs, which is less understood than contributors in the existing literature [9,32]. By understanding lurkers as observers with similar psychological scaffolding, this study finds that lurkers can gain self-efficacy and motivation to learn by observing the successful contributions of other users in the community.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…This study provides a theoretically grounded explanation and offers a new perspective on the underlying nature of lurkers in OICs, which is less understood than contributors in the existing literature [9,32]. By understanding lurkers as observers with similar psychological scaffolding, this study finds that lurkers can gain self-efficacy and motivation to learn by observing the successful contributions of other users in the community.…”
mentioning
confidence: 84%
“…Previous studies have shown that the users' recognized participation in OIC significantly increases their performance and engagement, which further promotes knowledge contribution behavior [9,31,48]. Panda and Mohapatra [14] concluded that outcome ex-pectancy has a significant positive impact on user knowledge sharing behavior.…”
Section: Self-efficacy Outcome Expectancy and Knowledge Contributionmentioning
confidence: 97%
See 3 more Smart Citations